2022
DOI: 10.1101/2022.06.03.494689
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

RPG acts as a central determinant for infectosome formation and cellular polarization during intracellular rhizobial infections

Abstract: Host-controlled intracellular accommodation of nitrogen-fixing bacteria is essential for the establishment of a functional Root Nodule Symbiosis (RNS). In many host plants, this occurs via transcellular tubular-structures (infection threads - ITs) that extend across cell layers via polar tip-growth. Comparative phylogenomic studies have identified RPG (RHIZOBIUM-DIRECTED POLAR GROWTH) among the critical genetic determinants for bacterial infection. In Medicago truncatula, RPG is required for effective IT progr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 86 publications
0
9
0
Order By: Relevance
“…In this study, we found that RPG was localized in puncta, some of which were close to the nucleus in N. benthamiana leaves and L. japonicus root protoplasts. A very recent study in M. truncatula showed that the IT tip-to-nucleus microtubule connectivity is perturbed in rpg-1 [55]. Together, all these studies strongly indicated that RPG plays an important role in nuclear-led IT elongation.…”
Section: Discussionmentioning
confidence: 72%
“…In this study, we found that RPG was localized in puncta, some of which were close to the nucleus in N. benthamiana leaves and L. japonicus root protoplasts. A very recent study in M. truncatula showed that the IT tip-to-nucleus microtubule connectivity is perturbed in rpg-1 [55]. Together, all these studies strongly indicated that RPG plays an important role in nuclear-led IT elongation.…”
Section: Discussionmentioning
confidence: 72%
“…Although the mixed step of intracellular accommodation including the release of symbiosomes and their persistence in the Medicago and Mimosa dataset displays a peculiar evolutionary pattern (see below and Figure 3), this symbiotic stage also involved genes that are part of the ancestral transcriptomic response. Suppressors of plant defense in nodules, SYMCRK 55 and RSD 56 , as well as the transcription regulator EFD required for both plant and bacteroid differentiation in Medicago 57,58 the M. pudica data, we found VAPYRIN, RPG, some flotillin and remorin genes and the syntaxin SYN, which are well-known infection-associated genes 33,[59][60][61] . We thus hypothesize that a proportion of genes linked with the ancestral RNS transcriptome and associated with intracellular accommodation reflects infection (Figure 4C).…”
Section: Gradual Recruitment Of Plant Symbiotic Gene Expression In Ex...mentioning
confidence: 63%
“…Suppressors of plant defense in nodules, SYMCRK 55 and RSD 56 , as well as the transcription regulator EFD required for both plant and bacteroid differentiation in Medicago 57,58 participate to this ancestral response. Looking specifically at the M. pudica data, we found VAPYRIN, RPG, some flotillin and remorin genes and the syntaxin SYN, which are well-known infection-associated genes 33,5961 . We thus hypothesize that a proportion of genes linked with the ancestral RNS transcriptome and associated with intracellular accommodation reflects infection (Figure 4C).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…In this study, we found that RPG was localized in puncta close to the nucleus in N. benthamiana leaves and L. japonicus root protoplasts. A very recent study in M. truncatula showed that the IT tip-to-nucleus microtubule connectivity is perturbed in rpg-1 (Lace et al, 2022). Together all these studies strongly indicated that RPG plays important roles in nuclear-led IT elongation.…”
Section: Discussionmentioning
confidence: 99%